Role of Sb dopant in Ag:GeSx‐based conducting bridge random access memories. Issue 2 (2nd December 2015) - d'Acapito, F.; Souchier, E.; Noé, P.; Blaise, P.; Bernard, M.; Jousseaume, V.
Abstract : The local structure around Sb dopants in the electrolyte of conducting bridge random access memories with Ag:GeS x composition has been investigated by grazing incidence X‐ray absorption spectroscopy (GIXAS). Sb is shown to be strongly bound to the matrix via bonds to S ions and a well‐defined second coordination shell. The GIXAS analysis on Ag revealed an increased amount of metallic Ag in samples containing Sb. These data explain the improved behaviour, in terms of data retention, of this class of materials upon Sb addition.